El dibujo de los niños de la Institución Educativa Inicial N°62084 Oculiza Alto Amazonas Balsapuerto 2022 - Maricahua Cahuasa, Mari Luz (2024)
The primary objective of this research is to determine the level of drawing development in children at the Initial Educational Institution No. 62084 Oculiza, Alto Amazonas, Balsapuerto, in the year 2022. To achieve this, a descriptive approach was utilized, with a non-experimental and cross-sectional design. The population consisted of 41 children from the same institution, meaning all students were included in the study. The technique employed was observation, and a structured observation guide was used for data collection. Additionally, the validity of the instruments was verified through expert evaluation. The results reveal an equitable distribution between children with achieved drawing skills and those in the developmental process, indicating a diversity in the level of progress. Most children have satisfactorily reached the scribbling level, although there are still cases requiring personalized attention. In the pre-schematic level, more than half of the group has shown progress, though significant individual differences exist. The lack of consolidation in the schematic level and the small number of children who have reached the beginnings of realism suggest that a more specialized approach is needed for drawing development.